2011
DOI: 10.1111/j.1365-246x.2011.05030.x
|View full text |Cite
|
Sign up to set email alerts
|

Inclination variation in the Late Jurassic to Eocene red beds from southeast Asia: lithological to locality scale approach

Abstract: S U M M A R YShallow palaeomagnetic inclinations have been frequently reported from the red beds of central and southeast Asia. To trace the origin of this phenomenon, inclination variation in southeast Asia is examined on lithological to locality scale. Lithological aspect of this variation has been studied using the Early Cretaceous Bailong and Cangxi formations of the Bazhong area (32.1 • N, 106.7 • E), the northern Sichuan Basin. Samples from 36 sites, consisting 18 pairs of successive sandstones and mudst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 121 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…These are compatible to a difference between the observed and expected Cretaceous inclinations (7.4 • ± 2.6 • ) reported from the Shan-Thai Block (K1 and K2 in Table 2), which has been declared primary as a result of the positive fold test. This compatibility between the present and previously reported data sets (Sato et al 2011) confirm a widespread presence of steep inclinations in the region, which tectonically suggest a southward displacement of the Shan-Thai Block (Leloup et al 1995).…”
Section: Reliability Of the Present Palaeomagnetic Resultssupporting
confidence: 92%
“…These are compatible to a difference between the observed and expected Cretaceous inclinations (7.4 • ± 2.6 • ) reported from the Shan-Thai Block (K1 and K2 in Table 2), which has been declared primary as a result of the positive fold test. This compatibility between the present and previously reported data sets (Sato et al 2011) confirm a widespread presence of steep inclinations in the region, which tectonically suggest a southward displacement of the Shan-Thai Block (Leloup et al 1995).…”
Section: Reliability Of the Present Palaeomagnetic Resultssupporting
confidence: 92%
“…Even though the site mean direction of the Jingzhushan Formation passes McElhinny (1964) fold test, the mean inclination calculated from 31 paleomagnetic sites of the northern limb of folds ( I s = 19.0°) is significantly lower than that of 23 paleomagnetic sites of the southern limb of folds ( I s = 51.8°) (Table 1). This large discrepancy of the mean inclination of the two limbs of folds may be attributed to several factors: (1) the depositional and/or compaction of sedimentary rocks may cause the inclination shallowing (Ding et al, 2015; Kodama, 2012; Tan et al, 2010; Tauxe & Kent, 2004); (2) the original strata were not horizontal but inclined when the sedimentary rocks got magnetization, so the inclination obtained from the two limbs of folds was quite different (Sato et al, 2011; Tong et al, 2019); (3) the chemical remanent magnetization (CRM) was acquired after deposition of the red beds, which can obscure the primary component (Jiang et al, 2015; Kodama & Dekkers, 2004); (4) the remanence directions obtained from the two limbs of folds may have been influenced by the distortional strains (Cogné et al, 1991; Kanamatsu & Herrero‐Bervera, 2006; Kligfield et al, 1983). The above four possibilities are discussed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Because the paleomagnetic data sets used to construct the apparent polar wander path (APWP) of East Asia (Cogné et al, ) contain Cretaceous and Paleogene paleomagnetic data from the Sichuan Basin, the Cretaceous pole of the eastern edge of SCB is considered more appropriate for paleomagnetic studies of southwestern China (Tong, Sun, et al, ; Wang et al, ). In addition, the Cenozoic rotational deformation of the edge of the Sichuan Basin is much smaller than that of the southeastern edge of the Tibetan Plateau (Enkin, Chen, et al, , Enkin, Courtillot, et al, ; Sato et al, ; Tong, Sun, et al, ; Wang et al, ; Zhao et al, ). Thus, it is necessary to compare the amount of rotation calculated using the different APWPs of Europe (Besse & Courtillot, ; Torsvik et al, ) and the eastern edge of SCB (Tong, Sun, et al, ), respectively, in order to confirm whether the rotational characteristics relative to the different reference poles would change.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Cenozoic crustal kinematic characteristics of the Sichuan Basin are still been strongly debated. During the past three decades, numerous paleomagnetic data obtained from the Cretaceous and Cenozoic red‐beds on the edge of the Sichuan Basin, such as the Bazhong and Tongjiang‐Wanyuan area on the northern edge (Sato et al, ; Wang et al, ; Zhao et al, ), the Yaan and Xinjin areas on the southwestern and western edges, respectively (Otofuji et al, ; Enkin, Chen, et al, , Enkin, Courtillot, et al, ; Zhao et al, ), and the Yibin area on the southern edge (Tong, Sun, et al, (Figure a), have revealed contradictory kinematic characteristics of clockwise or counterclockwise rotational deformation. Wang et al () suggested that the activity of the Xianshuihe strike‐slip fault drove the Sichuan Basin to experience integral counterclockwise rotational movement since ~13 Ma, which controlled the right‐lateral strike‐slip movement of the northeastern segment of the LMSFB.…”
Section: Introductionmentioning
confidence: 99%